2013
DOI: 10.1186/1475-2875-12-178
|View full text |Cite
|
Sign up to set email alerts
|

Hyperendemic malaria transmission in areas of occupation-related travel in the Peruvian Amazon

Abstract: BackgroundPlasmodium vivax and Plasmodium falciparum cause a significant illness burden in Peru. Anopheline indices for populated communities in the peri-Iquitos region of Loreto have been reported to be remarkably low, with entomological inoculation rates (EIR) estimated at one to 30 infective bites per year based on a few studies in close proximity to the urban centre of Iquitos and surrounding deforested areas. Local reports suggest that a large number of the reported cases are contracted outside of populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 28 publications
5
90
0
3
Order By: Relevance
“…Despite the fact that Loreto has been considered to be hypoendemic for malaria transmission,16 routine surveillance data and epidemiological studies suggest that malaria transmission in the region is highly heterogeneous, with some areas in relatively remote Amazonia having entomological inoculation rates (EIRs) rivaling those found in holoendemic regions of Africa 19. More than 80% of the total malaria clinical cases detected by PCD in Loreto are concentrated among only 10–20% of the total communities of the department 6.…”
Section: Peruvian P Vivax-endemic Regionsmentioning
confidence: 99%
“…Despite the fact that Loreto has been considered to be hypoendemic for malaria transmission,16 routine surveillance data and epidemiological studies suggest that malaria transmission in the region is highly heterogeneous, with some areas in relatively remote Amazonia having entomological inoculation rates (EIRs) rivaling those found in holoendemic regions of Africa 19. More than 80% of the total malaria clinical cases detected by PCD in Loreto are concentrated among only 10–20% of the total communities of the department 6.…”
Section: Peruvian P Vivax-endemic Regionsmentioning
confidence: 99%
“…Malaria transmission in the Amazon is promoted by several factors: anthropogenically-driven habitat change-for example, agriculture, logging, and mining-resulting in changes in vector breeding sites including urbanization 14,15 ; immigration of nonimmune humans into rural settlements in new frontier sites 16,17 ; and asymptomatic carriers. 18 Gold mining leads to several of these conditions, including habitat modification 19,20 and human settlements in the Amazon frontier.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, of those workers tested for malaria, 88% of positive cases were asymptomatic at the time of sampling. These EIR rates are much higher than those of other peri-Iquitos studies focusing on deforested areas, bringing attention to potential malaria hot spots and transmission from frequently exposed asymptomatic workers to families and communities located in areas with much lower transmission rates (139). This reinforces the potential danger for the spread of malaria if An.…”
Section: In Perumentioning
confidence: 60%
“…A study by Parker et al (2013) showed extremely high levels of malaria transmission in remote areas of human occupation. Sites along the Mazan River, utilized by many laborers to fish, extract wood, and harvest palm leaves used in thatched roof construction, showed entomological inoculation rates (EIR) as high as 5.3 infective bites/person/night (EIRs showed a seasonality).…”
Section: In Perumentioning
confidence: 99%